(3cGTa GdZeI Yf MSf SjQI EeGe GdCFeI GdfGUQ eMeO Hf GdegOi dOjf Gddg Ydi Hf eMeOs - (3GdgGOj Hf EHQGgje Hf Ydj Hf GdeQJVj GdMSjfj Hf GdhRjQ,LeGd GdOjf , GHf GdhRjQ, J (B822 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aJb Yf bdhH ChdjGFg CZTjg CceGe GdSfI hHYO GdHGYK Ydi QSe gYPg GdCMQa GdeNJUQI SDGdc CjgG Gdabjg Ydi Hf jMji GdTQai eQJHkG Ydi CQHYI CbSGe GdChd ai aVd ehdGfG Ydi SHjd GdLedI s
(3BNQgG (B:s
(3bGd eDda GdQSGdI fLR GdZQV ef EedGA gPg GdQSGdI GdeHGQcI s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eUMMIs
(3Ydi WQJgG eWGdYGJ hJedcGJ hHChdgG hUjI GdEeGe GdgGOi Edi GdMb jMji Hf GdMSjf s
(3HBNQgG eWGdYI eDQNI (B112(3g` hgj ef cJH GdSjO eMeO Hf eMeO GdefUhQ UfYGA s
(3bQf GdfSN (B:s
Keywords: (3Gdabg GdESdGejs